2014
DOI: 10.1016/j.cageo.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Automatic decision support system based on SAR data for oil spill detection

Abstract: Global trade is mainly supported by maritime transport, which generates important pollution problems. Thus, effective surveillance and intervention means are necessary to ensure proper response to environmental emergencies. Synthetic Aperture Radar (SAR) has been established as a useful tool for detecting hydrocarbon spillages on the oceans surface. Several Decision Support Systems have been based on this technology. This paper presents an automatic oil spill detection system based on SAR data which was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Many researchers tried to study the relative importance of features for feature selection, but their conclusions are not in consistency due to their different experiment settings. For example, Karathanassi et al [19] grouped 13 features into sea state dependent features and sea state independent features; Topouzelis et al [7,8] examined 25 most commonly used features based on neural networks and decision tree forest, and selected several feature-subsets that are of most importance; Mera et al [15] applied principal component analysis (PCA) to 17 shape related features and finally selected 5 principal components for their automatic oil spill detection system; and Xu et al [22] implemented the permutation-based variable accuracy importance (PVAI) technique to evaluate feature's importance relative to different criteria and they found that different types of classifier tended to present different patterns on feature ranking and PVAI values.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers tried to study the relative importance of features for feature selection, but their conclusions are not in consistency due to their different experiment settings. For example, Karathanassi et al [19] grouped 13 features into sea state dependent features and sea state independent features; Topouzelis et al [7,8] examined 25 most commonly used features based on neural networks and decision tree forest, and selected several feature-subsets that are of most importance; Mera et al [15] applied principal component analysis (PCA) to 17 shape related features and finally selected 5 principal components for their automatic oil spill detection system; and Xu et al [22] implemented the permutation-based variable accuracy importance (PVAI) technique to evaluate feature's importance relative to different criteria and they found that different types of classifier tended to present different patterns on feature ranking and PVAI values.…”
Section: Datasetmentioning
confidence: 99%
“…The class label of a test sample is predicted by applying the decision criteria from the root to the leaves to determine which leaf it falls in. Because of its capability of easily providing an intelligible model of the data, decision tree is very popular and widely used for classification purpose either directly [3,15] or as the elemental classifier of state-of-the-art ensemble techniques such as bagging, bundling and boosting for achieving better generality performance [8,22,[54][55][56]. Here, we use the DT supported by the classification and regression tree (CART) algorithm [53].…”
Section: Decision Treementioning
confidence: 99%
“…There are two ways in which to approach the oil-spill detection problem: studying the characterization of the slick by means of the multi-polarization features of SAR techniques, as occurs in [ 5 , 6 , 7 ], or using the brightness image obtained from the backscatter signal without considering the parameters of the processes of image acquisition and formation, as in [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Our work falls within the second category.…”
Section: Introductionmentioning
confidence: 99%
“…Oil spills are environmental disasters that most often lead to negative important factors on aquaculture, sea grasses, coral reefs, desalination plants, fish industrial, seashell and crab farms, and tourism activities [30]. Many studies on oil spills detection and analysis have been conducted in most of the main seas and oceans with different satellites and methods: Li [30], Simecek-Beatty [31], Lardner [32], Guo [33], Mera [34], Romero [35].…”
Section: Introductionmentioning
confidence: 99%